Financial Ratio to Predicting the Growth Income (Case Study: Pharmaceutical Manufacturing Company Listed on Indonesia Stock Exchange Period 2012 to 2016) - Nugroho, Edi Suswardji; Nurdiansyah, Dian Hakip; Erviana, Nita (International Review of Management and Marketing, 2017)
Increasing business competition causes companies to compete in order to improve their production to develop the company. Funding becomes one of the important factors. Before making a decision to invest. Therefore, investors need various information as a guide to decide the investment in capital market. Profit is one the potential information contained in the financial statement that is mostly used to determine the success or failure of corporate management. The variables in this research consist of current ratio (CR), debt to equity ratio (DER) and net profit margin (NPM) as independent variable and profit growth as the dependent variable. The sample used is a pharmaceutical manufacturing company listed in the Indonesia Stock Exchange which has a complete annual financial report during the observation period (2012-2016). The analysis used is descriptive quantitative method, through descriptive statistical analysis, classical assumption test, multiple linear regression test and hypothesis test. Based on the test result, it is proven that the CR, DER and DER influence the prediction of the profit growth of 33.80% simultaneously. Partially, CR has no effect on predicting profit growth, DER and DER has positive effect on predicting earnings growth. Keywords: Current Ratio, Manufacturing Company, Profit Growth JEL Classification: G140